Pore Structure and Wettability of Lacustrine Shale With Carbonate Interlayers in Dongying Depression, Bohai Bay Basin, East China - Yin, N.; Hu, Q. H.; Liu, H. M.; Du, Y. S.; Zhu, X. C.; Meng, M. M. (Frontiers in Earth Science, 2022)
Shale samples with carbonate interlayers have attracted more and more attention in shale oil exploration of lacustrine shale in China, and the characterization of pore structure and wettability of these shales are significant to the study of shale-oil enrichment and effective exploitation. In this work, by examining six shale samples with carbonate interlayers of Shahejie Formation in East China, the pore structure and wettability characteristics of shale are characterized by means of thin section petrography, X-ray diffraction mineralogy, total organic carbon (TOC) analyses, scanning electron microscopy (SEM) imaging, air-liquid contact angle for wettability, as well as N2 physisorption, mercury intrusion porosimetry, and nuclear magnetic resonance (NMR) for pore structure. The results show that the main mineral contents are carbonate (with an average of 51.4%) and clay minerals (mainly mixed-layer illite-smectite). The average TOC content is 2.90%, and there is a strong correlation between TOC and dolomite content. In addition, the obvious layered structure is observed by thin section and SEM methods. The pores below 200 nm with ink-bottle shapes are obviously smaller than those of marine shale, and the pore throats are mainly below 50 nm; however, there are also some μm-sized cracks. The drop-let contact angle measurement shows that the shale is mainly lipophilic, while moderately hydrophilic, at mm observational scales. The NMR T2 spectra of water- and oil-saturated samples have an obvious feature of three peak characteristics, as the pore size-associated wettability of these samples can be divided into 3 stages: water–wet (0.01–1 ms), oil-wet (1–40 ms), and mixed-wet (>40 ms) in terms of relaxation time of the NMR T2 spectrum. The proportion of the second main peak of T2 spectra (P2) for dodecane-saturated samples is directly proportional to the TOC content, and the relationship between P2 and mineral composition is consistent with water-saturated samples.